Screening robust water infrastructure investments and their trade-offs under global change: A London example - Huskova, Ivana; Matrosov, Evgenii S.; Harou, Julien J.; Kasprzyk, Joseph R.; Lambert, Chris (Global environmental change, 2016)
•A screening approach for robust water resource intervention portfolios is proposed.•The proposed multi-scenario trade-off analysis identifies robust investments.•Intervention portfolios differ in their ability to cope with varying conditions.•Portfolios identified using historical conditions often fail under future scenarios.•Visualizing performance trade-offs helps explore robust investments. We propose an approach for screening future infrastructure and demand management investments for large water supply systems subject to uncertain future conditions. The approach is demonstrated using the London water supply system. Promising portfolios of interventions (e.g., new supplies, water conservation schemes, etc.) that meet London’s estimated water supply demands in 2035 are shown to face significant trade-offs between financial, engineering and environmental measures of performance. Robust portfolios are identified by contrasting the multi-objective results attained for (1) historically observed baseline conditions versus (2) future global change scenarios. An ensemble of global change scenarios is computed using climate change impacted hydrological flows, plausible water demands, environmentally motivated abstraction reductions, and future energy prices. The proposed multi-scenario trade-off analysis screens for robust investments that provide benefits over a wide range of futures, including those with little change. Our results suggest that 60 percent of intervention portfolios identified as Pareto optimal under historical conditions would fail under future scenarios considered relevant by stakeholders. Those that are able to maintain good performance under historical conditions can no longer be considered to perform optimally under future scenarios. The individual investment options differ significantly in their ability to cope with varying conditions. Visualizing the individual infrastructure and demand management interventions implemented in the Pareto optimal portfolios in multi-dimensional space aids the exploration of how the interventions affect the robustness and performance of the system.